Tensile Strength, Elasticity and Cracking Character of Softwood Tissues - Kristina Ukvalbergienė; Viktorija DAKNEVIČIŪTĖ; Daiva MILAŠIENĖ (Medžiagotyra, 2015)
Wood tensile strength in longitudinal direction depends on wood density and structure. Growth rings in wood consist of earlywood and latewood which differ greatly in their properties. Latewood is denser, less porous and more resistant to tension along the fiber compared earlywod. The ratio of latewood and earlywood is different for each type of wood species and also depends on growing conditions, climate and etc. The study is aimed to evaluate the tensile strength, elasticity and cracking character of Lithuanian-grown softwood tissues, depending on the wood species, tissue width and latewood ratio in the sample. For the study three species of wood (spruce, pine and larch) were chosen. Samples were cut with the microtome, tissues cross-sectional area of about 0.15-0.50 mm2. The ratio of latewood and earlywood was evaluated using microscope. Wood tissue tensile strength was tested in the tensile machine with a feed rate of 0.2 mm/min. Research results showed that the highest tensile strength was obtained for larch wood samples, while the spruce wood most tended to deformation. Ir was determined that the tensile strength and elasticity of wood are highly influenced by wood microstructure and earlywood and latewood ratio in the sample. Also the wood microstructure and failure mechanism of the samples were evaluated. DOI: http://dx.doi.org/10.5755/j01.ms.21.2.6881